2013
DOI: 10.1513/annalsats.201211-092oc
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Nurses’ Perception of Time Spent at Rapid Responses

Abstract: In this study of one midsized academic medical center, about half of critical care nurse involvement in RRs takes them away from their ICU patients for less than 20 minutes. Nevertheless, nurses felt that ICU care was compromised when an ICU nurse responded to an RR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In our study, RRT nurses' feelings of setting the ICU patient aside to fulfil RRT obligations, and of facing heavy workloads were also identified and supported by others. Wang et al ( 2013 ) reported that ICU nurses felt ICU care was compromised when a nurse attended a RRT call. In a study by Tirkkonen et al ( 2018 ), RRT nurses felt their workload to be heavier than that of their ICU colleagues who were not doing RRT.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, RRT nurses' feelings of setting the ICU patient aside to fulfil RRT obligations, and of facing heavy workloads were also identified and supported by others. Wang et al ( 2013 ) reported that ICU nurses felt ICU care was compromised when a nurse attended a RRT call. In a study by Tirkkonen et al ( 2018 ), RRT nurses felt their workload to be heavier than that of their ICU colleagues who were not doing RRT.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, adverse events may occur in ICU patients while critical care staff are on RRT calls [13]. Importantly, cost savings associated with preventing unplanned ICU admissions may in itself justify the funding of a hospital-wide RRS [14].…”
Section: Resource Considerationsmentioning
confidence: 99%
“…Intensive Care Units (ICUs) are special departments of a hospital or healthcare facility that provide critically ill or critically injured patients with intensive medical treatment, under the close supervision of specially-trained medical staff. ICUs are distinguished from normal hospital wards by a higher staff-to-patient ratio (often a 2:1 nurse to patient ratio) [20], by access to advanced medical resources and equipment that is not routinely available elsewhere, and by access to staff with often complementary expertise. Because the ICU patients require continuous monitoring, multiple teams rotate responsibilities: each interdisciplinary team provides care for 12–18 hour shifts before they transfer the patient care responsibilities to the next critical care team.…”
Section: Introductionmentioning
confidence: 99%